Changes in Eicosanoid and Tumour Necrosis Factor-α Production by Rat Peritoneal Macrophages During Carrageenin-Induced Peritonitis - W. M. Pruimboom; A. Verdoold; C. J. A. M. Tak; A. P. M. van Dijk; M. van Batenburg; J. H. P. Wilson; F. J. Zijlstra (Hindawi Limited, 1994)
Changes and correlations in cytokine and eicosanoid production by blood monocytes, non-purified and purified peritoneal cells during a carrageenin-induced peritonitis were investigated for a period of ten days. The cells were isolated and stimulated in vitro. Cytokine and eicosanoid production of the non-purified fraction increased steadily during peritonitis. During the whole episode of peritonitis the production capacity of granulocytes was very low and hardly any effect on the production capacity of macrophages (Mϕ) was observed. Cytokine and eicosanoid production of the non-purified fraction was mainly due to the presence of Mϕ. The production capacity of the peripheral blood monocytes was not similar to that of the peritoneal Mϕ.